Alkali-Metal-Templated Self-Assembly of Nickel(II) [12-MC-3] Metallacoronates Based on Bis(pyrazol-1-yl)acetato Ligands - Beyer, Andreas; von Gernler, Marc; Pflock, Stephan; Türkoglu, Gazi; Müller, Lisa; Zahl, Achim; Gieb, Klaus; Müller, Paul; Drewello, Thomas; Burzlaff, Nicolai (Chemistry - A European Journal, 2018)
Keywords: Metallacrowns; Nickel; Acetyl acetonate; Template synthesis; Tripodal ligands

Carbon-rich cyclopentadienyl ruthenium allenylidene complexes - Spörler, Susanne; Strinitz, Frank; Rodehutskors, Philipp Maximilian; Müller, Lisa; Waterloo, Andreas; Dürr, Maximilian; Hübner, Eike; Ivanovic-Burmazovic, Ivana; Tykwinski, Rik; Burzlaff, Nicolai (New Journal of Chemistry, 2016)
Ruthenium allenylidene complexes with carbon-rich polyaromatic moieties have been synthesized by using [RuCl(η-CH)(PPh)] (η-CH = cyclopentadienyl) as a precursor and the propargyl alcohols 10-ethynyl-10-hydroxyanthracen-9-one (ACO), 13-ethynyl-13-hydroxypentacen-6-one (PCO), 1-phenyl-1-(pyren-1-yl)prop-2-yn-1-ol (PyrPh), 9-ethynyl-9H-fluoren-9-ol (FN) and 6-ethynyl-6H-benzo[cd]pyren-6-ol (BPyr) as ligands. The resulting cationic allenylidene complexes, [Ru(η-CH)(CC(AO))(PPh)]PF (1), [Ru(η-CH)(CC(PCO))(PPh)]PF (2), [Ru(η-CH)(CC(PyrPh))(PPh)]PF (3), [Ru(η-CH)(CC(FN))(PPh)]PF (4), and [Ru(η-CH)(CC(BPyr))(PPh)]PF (5) show interesting intermolecular π-interactions in the solid-state structure as well as solution state complexation with pyrene (documented by Job's plots experiments). CV data indicate possible Ru(ii)/Ru(iii) oxidation, as well as the potential reduction of the carbon-rich allenylidene moiety.

Hyperoxaluria Requires TNF Receptors to Initiate Crystal Adhesion and Kidney Stone Disease - Mulay, Shrikant R.; Eberhard, Jonathan N.; Desai, Jyaysi; Marschner, Julian A.; Kumar, Santhosh V.R.; Weidenbusch, Marc; Grigorescu, Melissa; Lech, Maciej; Eltrich, Nuru; Müller, Lisa; Hans, Wolfgang; Hrabě de Angelis, Martin; et al. (Journal of the American Society of Nephrology, 2016)
Intrarenal crystals trigger inflammation and renal cell necroptosis, processes that involve TNF receptor (TNFR) signaling. Here, we tested the hypothesis that TNFRs also have a direct role in tubular crystal deposition and progression of hyperoxaluria-related CKD. Immunohistochemical analysis revealed upregulated tubular expression of TNFR1 and TNFR2 in human and murine kidneys with calcium oxalate (CaOx) nephrocalcinosis-related CKD compared with controls. Western blot and mRNA expression analyses in mice yielded consistent data. When fed an oxalate-rich diet, wild-type mice developed progressive CKD, whereas Tnfr1-, Tnfr2-, and Tnfr1/2-deficient mice did not. Despite identical levels of hyperoxaluria, Tnfr1-, Tnfr2-, and Tnfr1/2-deficient mice also lacked the intrarenal CaOx deposition and tubular damage observed in wild-type mice. Inhibition of TNFR signaling prevented the induced expression of the crystal adhesion molecules, CD44 and annexin II, in tubular epithelial cells in vitro and in vivo, and treatment with the small molecule TNFR inhibitor R-7050 partially protected hyperoxaluric mice from nephrocalcinosis and CKD. We conclude that TNFR signaling is essential for CaOx crystal adhesion to the luminal membrane of renal tubules as a fundamental initiating mechanism of oxalate nephropathy. Furthermore, therapeutic blockade of TNFR might delay progressive forms of nephrocalcinosis in oxalate nephropathy, such as primary hyperoxaluria.
EVALuna2:13343

The macrophage phenotype and inflammasome component NLRP3 contributes to nephrocalcinosis-related chronic kidney disease independent from IL-1-mediated tissue injury - Anders, Hans-Joachim; Suarez-Alvarez, Beatriz; Grigorescu, Melissa; Foresto-Neto, Orestes; Steiger, Stefanie; Desai, Jyaysi; Marschner, Julian A.; Honarpisheh, Mohsen; Shi, Chongxu; Jordan, Jutta; Müller, Lisa; Burzlaff, Nicolai; et al. (Kidney International, 2018)
Primary/secondary hyperoxalurias involve nephrocalcinosis-related chronic kidney disease (CKD) leading to end-stage kidney disease. Mechanistically, intrarenal calcium oxalate crystal deposition is thought to elicit inflammation, tubular injury and atrophy, involving the NLRP3 inflammasome. Here, we found that mice deficient in NLRP3 and ASC adaptor protein failed to develop nephrocalcinosis, compromising conclusions on nephrocalcinosis-related CKD. In contrast, hyperoxaluric wild-type mice developed profound nephrocalcinosis. NLRP3 inhibition using the ?-hydroxybutyrate precursor 1,3-butanediol protected such mice from nephrocalcinosis-related CKD. Interestingly, the IL-1 inhibitor anakinra had no such effect, suggesting IL-1-independent functions of NLRP3. NLRP3 inhibition using 1,3-butanediol treatment induced a shift of infiltrating renal macrophages from pro-inflammatory (CD45F4/80CD11bCX3CR1CD206) and pro-fibrotic (CD45F4/80CD11bCX3CR1CD206TGF?) to an anti-inflammatory (CD45F4/80CD11bCD206TGF?) phenotype, and prevented renal fibrosis. Finally, in vitro studies with primary murine fibroblasts confirmed the non-redundant role of NLRP3 in the TGF-? signaling pathway for fibroblast activation and proliferation independent of the NLRP3 inflammasome complex formation. Thus, nephrocalcinosis-related CKD involves NLRP3 but not necessarily via intrarenal IL-1 release but rather via other biological functions including TGFR signaling and macrophage polarization. Hence, NLRP3 may be a promising therapeutic target in hyperoxaluria and nephrocalcinosis.
EVALuna2:154783